2020
DOI: 10.1007/s13592-020-00801-1
|View full text |Cite
|
Sign up to set email alerts
|

Sporopollenin as a dilution agent in artificial diets for solitary bees

Abstract: Nutritional studies often require precise control of nutrients via dilution of artificial diets with indigestible material, but such studies in bees are limited. Common diluents like cellulose typically result in total mortality of bee larvae, making quantitative studies difficult. We investigated potential alternative dietary dilution agents, sporopollenin (pollen exines) and agar. We reared Osmia bicornis larvae on pollen diluted with these substances, alongside undiluted controls. Sporopollenin neither prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Diets were diluted with sporopollenin, the primary constituent of the exine of pollen (Mackenzie et al, 2015) and an extraordinarily stable natural polymer, in the form of hollow capsules prepared in collaboration with Sporomex ® (sporo mex.co.uk) and crushed in a ball mill. Sporopollenin is known to be non-toxic to humans (Diego-Taboada et al, 2013), but is a novel dietary diluent for bees; we have demonstrated its suitability in a separate study (Tainsh et al, 2020). For a more detailed description of sporopollenin preparation, see supplementary methods.…”
Section: Diet Formulationmentioning
confidence: 77%
“…Diets were diluted with sporopollenin, the primary constituent of the exine of pollen (Mackenzie et al, 2015) and an extraordinarily stable natural polymer, in the form of hollow capsules prepared in collaboration with Sporomex ® (sporo mex.co.uk) and crushed in a ball mill. Sporopollenin is known to be non-toxic to humans (Diego-Taboada et al, 2013), but is a novel dietary diluent for bees; we have demonstrated its suitability in a separate study (Tainsh et al, 2020). For a more detailed description of sporopollenin preparation, see supplementary methods.…”
Section: Diet Formulationmentioning
confidence: 77%
“…Indeed, the effects of a poor diet are multifold. Pollen diversity and quality directly affect the colony development, the reproduction, and the physiology of bees [11,[26][27][28]. Furthermore, pollen provisions and access to pollen are directly linked, with any decreases in these two factors being shown to result in reduced body size, a key fitness component in pollinators [26,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…An exclusive diet of pollen was found to negatively affect development of zooplankton including D. longispina ; whereby the presence of microorganisms is required to degrade them to an intermediate trophic level (Masclaux et al 2011 ). As SpECs are empty capsules, they lack the nutritional component of intact grains and have been proposed as a dilution agent in artificial diets for arthropod larvae (Tainsh et al 2020 ). The effects of dietary dilution by SpECs on invertebrates are subject to further investigation.…”
Section: Resultsmentioning
confidence: 99%